DI-016 Development of a quick reference guide for syringe driver drug compatibilities. (24th March 2015) - McCabe, L; Kehoe, B
Abstract : Background: Drug administration via syringe driver is safe, simple, non-invasive and cost effective. A continuous subcutaneous (SC) infusion is used to provide symptom control in patients unable to tolerate oral administration, particularly in the palliative care setting. Various drug combinations are used in clinical practice and typically include opiates, anti-emetics, anxiolytics and anticholinergics. Many parenteral formulations of drugs may be suitable for subcutaneous administration however evidence and clinical experience with their use is lacking. In particular, information on the inherent risk of physical and/or chemical incompatibility associated with the process of mixing multiple parenteral drugs is neither readily accessible nor easily interpretable for frontline staff. In 2012, Medicines Information (MI) received 57 enquiries pertaining to the compatibility of parenteral drugs prescribed for continuous SC infusion via syringe pump, reflecting the need for a local reference compatibility chart. Purpose: To develop continuous SC infusion compatibility charts for the administration of 2- and 3-drug combinations. Material and methods: Review of previous MI enquiries relating to drug compatibility in syringe drivers. Search for available stability data on specific 2- and 3-drug combinations using past MI enquiries and palliative care resources. Compile the data and develop compatibility charts for commonly prescribed 2- and 3-drug combinations. Results: A continuous SC infusion 2- and 3-drug combination compatibility chart was developed. The 3-drug compatibility charts focused on morphine and fentanyl in combination with another two drugs. Conclusion: The administration of continuous SC infusions via syringe driver has become fundamental in symptom management within the palliative care setting. It is anticipated that these charts will enable frontline staff to readily access compatibility data at the time of prescribing. Monitoring of MI queries will continue to direct updating the resource to reflect hospital practice. References and/or acknowledgements: No conflict of interest.